(untitled) (Research, Society and Development, 2021)
With the quantifying and analyzing intention, the international scientific production on desertification, this article uses quantitative-descriptive analysis methods, through bibliometric studies, also using a database of platforms contained on the internet between the years 2015 to 2020. The information was obtained through the use of the data bank from Web of Science (WOS) Clarivate Analytics, and exported to the VosViewer 1.6.16 software, in order to measure the production of scientific knowledge, according to the survey of cataloged production indexes and to map certain indicators of the bibliometric network. The investigation found 220 publications containing the term “desertification” during the predetermined range of years. The obtained results revealed that in the year 2020 there was a greater quantity of publications, contrasting with the previous years. Among the scientific productions with the greatest impact, China stands out as the country with the largest number of published journals. English was the language chosen for the most articles, with a total of 90% writings. The use of VosViewer, in two analyzed indexes, increased the knowledge and understanding of the cluster’s formation of “co-citation networks” and of “co-authorship by countries”. It is believed that this research can contribute to further studies on the subject, given the importance of the parameters studied, not only for researchers, but also for society.